Making progress: Report of the Young Lives school survey in Vietnam - Dornan, P; James, Z (Young Lives, 2013)
Achieving universal access to good quality basic education is a key priority for Vietnam, as it is for other rapidly developing countries. Improving educational opportunities may be expected to play a role in reducing economic and social inequalities. However, attending school is only one set of influences on a child's learning development, and even in an equitable education system, home background and contextual influences may perpetuate or widen differences in learning progress between more and less advantaged pupils. This note is a summary of a longer research report, Making Progress: Report of the Young Lives School Survey in Vietnam. The analysis builds on the longitudinal survey of all the Young Lives children and their households (on-going, with data collected since 2002), with the addition of a school survey carried out during the school year 2011-12. Data was collected from 3,284 Grade 5 pupils, in 176 classes in 56 schools or 92 school sites (with satellite sites considered separately from the main school). All of the children completed an interview questionnaire and were tested in Mathematics and Vietnamese at both the start and end of the school year. Each test had 30 multiple choice questions, designed to test knowledge of the curriculum. Questions were of varying levels of difficulty making it easier to separate out low- and high-performing students. Both tests contained a number of common (anchor) items. This design makes it possible to answer key questions about children's learning and their learning progress as well as the effectiveness of schools and teachers in delivering progress in relation to the curriculum (often referred to as the "value-added" of schooling). The study was conducted in the 20 Young Lives study sites which are situated across five selected provinces (Ben Tre, Danang, Hung Yen, Lao Cai, and Phu Yen). The unique combination of longitudinal data about the children and their backgrounds and the focus on effective schooling adds to the evidence available in existing cross-sectional studies conducted by MOET and the World Bank, and is the first of its kind in Vietnam.